Water Practice & Technology - Water Practice & Technology (IWA Publishing, 2026)
Water Practice & Technology is a peer-reviewed journal that publishes papers on all practical aspects of water and wastewater treatment and management across the entire water cycle. It is primarily aimed at practitioners, while also being relevant to scientists, managers, and professionals involved in training and development.
FI 0.37
Q3
Keywords: Physical Sciences & Engineering; Water Resources; Recursos hídricos; Acuerdos transformativos; Transformative agreements; Gestión del agua; Aguas residuales; Ciclo de agua